التشكيل الرمزي في رواية "خطف الحبيب" لطالب الرفاعي - العايب، يوسف; فرطاس، محرز; نافع، عبد القادر; غريسي، بشير (University of Eloued جامعة الوادي, 2024)
تسعى هذه الدراسة إلى رصد تجليات الرمز في رواية " خطف الحبيب " و ذلك من خلال الجانب النظري لموضوع الدراسة , و جانب تطبيقي يتمثل في تحليل بعض الرموز الموظفة في الرواية , و مدلولات هذه الرموز. تناولت الرواية عدة قضايا شغلت و لا تزال تشغل راهن المجتمع العربي أهمها : التحاق الأبناء بالجماعات الإرهابية , و كذلك تصدع العلاقات الزوجية نتيجة للبرود العاطفي . كل هذه القضايا تطرق إليها و أبدع فيها طالب الرفاعي بأسلوب فني سردي , و لغة أدبية راقية. This study seeks to monitor the manifestations of the symbol in the novel “Kidnapping the Beloved” through the theoretical aspect of the subject of the study, and the practical aspect represented by the analysis of some of the symbols used in the novel, and the meanings of these symbols The novel dealt with several issues that preoccupied and continue to preoccupy Arab society, the most important of which are: children joining terrorist groups, as well as the rupture of marital relations as a result of emotional coldness All of these issues were addressed and excelled in by Talib Al-Rifai in an artistic narrative style and sophisticated literary language
813/ 013
Keywords: التشكيل ــــ الرمزي ـــــ خطف الحبيب ـــ طالب الرفاعي the manifestations-the symbol-Kidnapping the Beloved-Talib Al-Rifai